Lassa Fever Viral Replication, Disease Pathogenesis, and Host Immune Modulations - Ly, Hinh (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Lassa virus causes Lassa fever disease in several countries in West Africa, where it is estimated to infect up to half million people causing roughly five thousand deaths each year. This deadly virus has also been introduced in multiple occasions into the western world, including the United States, United Kingdom, Netherlands, Sweden, and Germany. Lassa virus infection, which is often misdiagnosed, can lead to a wide range of disease symptoms ranging from mild flu-like symptoms to bleeding disorders, multi-organ failure, and death. Despite some major discoveries made in recent years of research on Lassa fever, there are still many unresolved key issues that hamper the development of effective vaccines and therapies. Some of these issues include a detailed understanding of the viral and participating host factors in completing the virus life cycle, in mediating disease pathogenesis or protection, and in activating or suppressing host immune responses against virus infection. This book is devoted to understanding some of these important issues. Expert and timely contributions in the form of editorial and original research and review articles on Lassa fever viral replication, disease pathogenesis and protection, host immune modulations, and other related hot topics are presented in this publication.